Lebanon: between aspiration of changes and the ancient regime - Di Donato, Marco; Manduchi, Patrizia (RESOCONTI, 2022)
Irhal means: Leave! It is, as known, one of the most widespread slogans in the language of the so-called Arab uprisings, and it has been used as a slogan also in the Lebanese uprising of 2019. The focus of this report is the analysis of the political dynamics which have been shaking Lebanon since 2019, to try to understand the future prospects of this country which, after decades of dramatic political conflicts, is now undergoing to deep, protracted and overlapping (economic, social, political) crises, whose end is hard to see. The starting hypothesis is that today the dominant understanding of Lebanese socio-political divisions along sectarian lines needs to be re-considered. We argue that sectarian based socio-political divisions should not be considered as a result of immutable religious identities, but rather as the result of historicized cultural, material and political conditions and practices. Therefore, belonging to a sectarian socio-political group means primarily belonging to a "functional group", functional for example in terms of opportunities in education, access to services, healthcare, job placement. In this framework, this report aims to offer not only an analysis of current trends but also to contribute to give a positive perspective to the current debate, which is too often limited to geopolitical analyses without paying close attention to young students and academics as protagonists of social and civil life who can act as promoters of change, as we have learned from 2011 and 2019 in Lebanon. Lebanese youth's voices are, according to us, a very useful reading key to better understand the actual situation, allowing an analytical perspective "from below" of the dynamics of social transformation. The project "Lebanon: between aspiration of changes and the ancien regime" has been developed in the framework of the project IRHAL - For an analysis of the Lebanese protests and the role of the youth beyond the paradigm of confessionalism, financed by the Italian Ministry of Foreign Affairs and International Cooperation and coordinated by UNIMED.